Using a plant hormone and a thioligand to improve phytoremediation of Hg-contaminated soil from a petrochemical plant - Cassina, L.; Tassi, E.; Pedron, F.; Petruzzelli, G.; Ambrosini, P.; Barbafieri, M. (Journal of hazardous materials, 2012)
► Mercury uptake by crop plants grown on contaminated soil from a petrochemical site. ► Plant hormone increased biomass production while thioligand increased Hg uptake. ► The combination of cytokinine and ammonium thiosulfate showed synergistic effects on Hg phytoextraction. ► The labile Hg fraction in soil was significantly removed by Brassica juncea and Helianthus annuus. Mercury-contaminated soils from a petrochemical plant in southern Italy were investigated to assess the phytoextraction efficiency of crop plants treated with the phytohormone, cytokinine (CK foliar treatment), and with the thioligand, ammonium thiosulfate (TS, soil application). Plant biomass, evapotranspiration, Hg uptake and distribution in plant tissues following treatment were compared. Results indicate the effectiveness of CK in increasing plant biomass and the evapotranspiration rate while TS treatment promoted soil Hg solubility and availability. The simultaneous addition of CK and TS treatments increased Hg uptake and translocation in both tested plants with up to 248 and 232% in Brassica juncea (Indian mustard) and Helianthus annuus (sunflower) respectively. B. juncea was more effective in Hg uptake, whereas H. annuus gave better response regarding plant biomass production. The effectiveness of the treatments was confirmed by the calculation of Hg phytoextraction and evaluation of labile-Hg residue in the soil after plant growth. In one growing cycle the plants subject to simultaneous CK and TS treatment significantly reduced labile-Hg pools that were characterized by the soil sequential extraction, but did not significantly affect the pseudototal metal content in the soil. Results support the use of plant growth regulators in the assisted phytoextraction process for Hg-contaminated soils.